2021
DOI: 10.3390/insects13010034
|View full text |Cite
|
Sign up to set email alerts
|

Global Size Pattern in a Group of Important Ecological Indicators (Diptera, Chironomidae) Is Driven by Latitudinal Temperature Gradients

Abstract: Size is one of the most outwardly obvious characteristics of animals, determined by multiple phylogenetic and environmental variables. Numerous hypotheses have been suggested to explain the relationship between the body size of animals and their geographic latitude. Bergmann’s Rule, describing a positive relationship between the body size of endothermic animals and their geographic latitude, is especially well known. Whether or not insects exhibit a similar pattern has long been a subject for debate. We hypoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…According to Bergmann’s rule, the higher the temperature, the smaller the animal can be. This concept is usually applied to mammals, while for insects the mechanisms may differ, or there is no correlation 42 . At the same time, the authors suggested that the sizes of insects could expand with time simply due to random variation during the evolution of a group.…”
Section: Discussionmentioning
confidence: 99%
“…According to Bergmann’s rule, the higher the temperature, the smaller the animal can be. This concept is usually applied to mammals, while for insects the mechanisms may differ, or there is no correlation 42 . At the same time, the authors suggested that the sizes of insects could expand with time simply due to random variation during the evolution of a group.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to potential indirect effects on discharge, temperature is important to freshwater invertebrate growth, development and, as a consequence, body size. At large geographial scales, higher temperatures tend to correlate with smaller insect body sizes (Baranov et al, 2022; Bhowmik & Schäfer, 2015), even though there are documented exceptions to this rule (Atkinson, 1995). Higher water temperatures also can influence voltinism and cause earlier emergence times at a smaller body size (Anderson et al, 2019), although this is not always the case (McCauley et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Research related to conservation and environmental monitoring generates better insights when using taxonomic resolution at the genus or species levels (Lenat & Resh, 2001). Furthermore, for some groups such as Chironomidae, a more accurate taxonomic resolution is indicated for many applications in ecological research (Vasquez et al, 2022), to indicate phylogenetic structure (Baranov et al, 2021), and for the status Acta Limnologica Brasiliensia, 2022, vol. 34, e10…”
Section: Discussionmentioning
confidence: 99%